Complex Motion: First International Workshop, IWCM 2004, Günzburg, Germany, October 12-14, 2004. Revised Papers - Jähne, Bernd; Barth, Erhardt; Mester, Rudolf; Scharr, Hanno (Lecture notes in computer science, 2006)
Optical Flow Estimation from Monogenic Phase -- Optimal Filters for Extended Optical Flow -- Wiener-Optimized Discrete Filters for Differential Motion Estimation -- Boundary Characterization Within the Wedge-Channel Representation -- Multiple Motion Estimation Using Channel Matrices -- Divide-and-Conquer Strategies for Estimating Multiple Transparent Motions -- Towards a Multi-camera Generalization of Brightness Constancy -- Complex Motion in Environmental Physics and Live Sciences -- Bayesian Approaches to Motion-Based Image and Video Segmentation -- On Variational Methods for Fluid Flow Estimation -- Motion Based Estimation and Representation of 3D Surfaces and Boundaries -- A Probabilistic Formulation of Image Registration -- Myocardial Motion and Strain Rate Analysis from Ultrasound Sequences -- Determining the Translational Speed of a Camera from Time-Varying Optical Flow -- A Robust Approach for Ego-Motion Estimation Using a Mobile Stereo Platform -- Robust Monocular Detection of Independent Motion by a Moving Observer -- Tracking Complex Objects Using Graphical Object Models.